Post‐exercise cooling modified muscle performance and soreness perception. Issue 3 (4th February 2020) - Doeringer, Jeffrey R.; Colas, Megan; Khan, Irfan
Abstract: Athletes in recent years are to prophylactically use cold‐water immersion (CWI) 24 hours before a game, in hopes of improving performance and reduction of soreness. To assess the effects of pre‐ and post‐exercise CWI on muscle performance or pain perception. Twenty subjects enrolled in the study. Muscle performance measures included flexibility, strength, power, agility, and speed for the lower extremity. The subjects were pseudo‐randomly assigned to a CWI or control group. The independent variables were group (ice immersion vs control) and time (Baseline, 24 hours, and 48 hours). The dependent variables were muscle performance measurements and pain/soreness visual analog scale (VAS). A 2 × 3 mixed design ANOVA with repeated factors revealed a significant interaction for group × time for strength ( P  = .024), agility ( P  = .04), and VAS ( P  = .019). A post‐hoc independent sample t test revealed significant differences at 24 hours for strength ( P  = .001), 48 hours for agility ( P  = .03), and 48 hours for VAS ( P  = .001). There were no significant differences in flexibility, power, and speed between the CWI and control groups. The use of CWI 24 hours pre‐exercise improved strength, but improved agility 24 hours post‐exercise, and less muscle soreness when compared to the control group.